PENGARUH PROGRAM K3 DAN DISIPLIN KERJA TERHADAP KINERJA PETUGAS PEMADAM KEBAKARAN DI DINAS PEMADAM KEBAKARAN KABUPATEN BOGOR TAHUN 2020 - Wilda Dwi Apriliyani (2021)
Performance is something that is very important in an agency to achieve goals. The implementation of the K3 program and work discipline are important factors for improving employee performance. The purpose of this study is to see whether there is an influence between the K3 program and work discipline on improving performance. This research method is associative quantitative. The population studied was all 280 firefighters and rescue workers in Bogor Regency, a sample of 165 people was taken by purposive sampling. Data collection was done by filling out a questionnaire. In this study, a hypothesis test was carried out which included the F test (simultaneous test), t test (partial test), and multiple linear regression analysis. The results showed that there was an effect of the K3 program and work discipline together on performance where the value of Fcount = 200.571> from Ftable = 3.06 was obtained. The K3 program and work discipline together can influence the dependent variable of performance in the fire and rescue officers at the Bogor District Fire Service by 71.2%, while the remaining 28.8% is influenced by other variables not included in this study. It can be concluded that there is an influence between the K3 program and work discipline on the performance of firefighters. With this, fire department employees must always improve their existing performance in order to achieve the agency's goals.